The Influence Of Digital Finance, Financial Literacy, And Financial Inclusion On Debt Behavior Of Millenials - Deria Cahya Fitriadi; Dicky Jhoansyah; Resa Nurmala (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The abstract contains a brief description of the purpose: This study aims to determine the influence of digital finance, financial literacy, and financial inclusion on millennial debt behavior in Sukabumi City. This study is motivated by the increasing prevalence of online loans among millennials, which are often done without adequate financial planning or knowledge. Methods: Using a descriptive quantitative method with a cross-sectional survey design, this study collected primary data through a Likert-scale questionnaire distributed to 180 millennial respondents aged 29-44 years who have utilized online loan services. Data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS. Results: The results showed that digital finance, financial literacy, and financial inclusion have a simultaneous and statistically significant effect on debt behavior, with financial literacy showing the strongest individual contribution. All research instruments met the required validity and reliability standards, and the regression model met the assumptions of normality, multicollinearity, heteroscedasticity, and autocorrelation. underscore the important role of financial literacy and inclusion in promoting responsible debt behavior. underscore the important role of financial literacy and inclusion in promoting responsible debt behavior. Implications: of this study suggest the need for well-targeted financial education programs and a stronger regulatory framework for digital lending, especially among urban youth. Future research is recommended to adopt a longitudinal method or expand demographic coverage to improve generalizability.